2015
DOI: 10.1371/journal.pone.0136801
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 3 and 4 Complex Stimulates the Transcriptional Activity of the Mineralocorticoid Receptor

Abstract: Histone deacetylases (HDACs) act as corepressors in gene transcription by altering the acetylation of histones, resulting in epigenetic gene silencing. We previously reported that HDAC3 acts as a coactivator of the mineralocorticoid receptor (MR). Although HDAC3 forms complexes with class II HDACs, their potential role in the transcriptional activity of MR is unclear. We hypothesized that HDAC4 of the class II family stimulates the transcriptional activity of MR. The expression of MR target genes was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
(54 reference statements)
0
25
0
Order By: Relevance
“…In utero exposure to di-(2-ethylhexyl) phtalate leads to loss of methylation of MR gene promotor and reduced MR mRNA expression in testes (Martinez-Arguelles et al, 2009). Histone deacetylase 3 and 4 complexes have been reported to regulate MR transcriptional activity in cultured cells (Lee et al, 2015). Epigenetic mechanism may regulate MR expression via expression of microRNAs (miRNAs/miRs) and short regulatory RNAs.…”
Section: B Mechanisms Modulating Mineralocorticoid Receptormentioning
confidence: 99%
“…In utero exposure to di-(2-ethylhexyl) phtalate leads to loss of methylation of MR gene promotor and reduced MR mRNA expression in testes (Martinez-Arguelles et al, 2009). Histone deacetylase 3 and 4 complexes have been reported to regulate MR transcriptional activity in cultured cells (Lee et al, 2015). Epigenetic mechanism may regulate MR expression via expression of microRNAs (miRNAs/miRs) and short regulatory RNAs.…”
Section: B Mechanisms Modulating Mineralocorticoid Receptormentioning
confidence: 99%
“…First, HDAC4 interacts with multiple transcriptional factors [e.g., myocyte enhancer 2 (MEF2), runt related transcription factor 2 (Runx2), serum response factor (SRF), heterochromatin protein 1(HP1), nuclear factor kappa B (NF-κB)] regulating gene transcription (Sando et al, 2012; Ronan et al, 2013). Although HDAC4 per se lacks deacetylase activity, it may be involved in histone deacetylation-mediated transcriptional regulation via interacting with HDAC3, another member of the HDAC family with deacetylase activity (Grozinger et al, 1999; Lee et al, 2015). For example, Lee et al (2015) showed that HDAC4 is crucial for HDAC3-mediated deacetylation of mineralocorticoid receptor, which could be inhibited by class I HDAC inhibitor but not class II HDAC inhibitor, indicating that HDAC4 is implicated in protein deacetylation via the deacetylase activity of HDAC3.…”
Section: Hdac4 and Hdacsmentioning
confidence: 99%
“…Although HDAC4 per se lacks deacetylase activity, it may be involved in histone deacetylation-mediated transcriptional regulation via interacting with HDAC3, another member of the HDAC family with deacetylase activity (Grozinger et al, 1999; Lee et al, 2015). For example, Lee et al (2015) showed that HDAC4 is crucial for HDAC3-mediated deacetylation of mineralocorticoid receptor, which could be inhibited by class I HDAC inhibitor but not class II HDAC inhibitor, indicating that HDAC4 is implicated in protein deacetylation via the deacetylase activity of HDAC3. Moreover, the deacetylase activity of HDAC4 needs to be further investigated by multiple approaches as it is not convincing by the in vitro assay from one study (Lahm et al, 2007).…”
Section: Hdac4 and Hdacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee and coworkers (Lee et al 2015) have reported that the class II HDAC, HDAC4 mediates an interaction between HDAC3 and the MR, which coactivates aldosterone-induced, MR-mediated transactivation. Obradovic and coworkers (Obradovic et al 2004) sought to address the role of coregulators in conferring MR vs GR specificity in neurons where both receptors are responding to the same ligand, cortisol.…”
Section: Mr-specific Coregulatorsmentioning
confidence: 99%